Remote and local delivery of Cisco Education for the vision impaired - Armstrong, Helen; Murray, Iain (Association for Computing Machinery, 2007)
Vision-impaired students face tremendous obstacles in their quest to access learning materials delivered in web-based and other electronic formats. The predominance of visual prompts, use of flash and animation and the inability of screen reading applications to interpret images all contribute to make much of the current e-learning materials associated with computing studies inaccessible by blind or vision-impaired students. This paper describes a university research project undertaken to improve the accessibility of Cisco e-learning materials for vision-impaired computing students. The network architecture which supports the delivery of the Cisco courses to both local and remote vision-impaired students is also presented.